Visual Design and Souvenir Products National Development University "Veteran" East Java (UPN "Veteran" Jatim) as a “Bela Negara” Campus - Masnuna; Heidy Arviani (Nusantara Science and Technology Proceedings)
Visual design and souvenir products UPN "Veteran" of East Java is a research theme to introduce UPN "Veteran" of East Java as the campus “Bela Negara” (State Defense). UPN "Veteran" of East Java is the only state university that has the character of “Bela Negara”. However, the general public outside the campus not many people know about it. We try to introduce this character to general public and academic community. Since 2010 “Bela Negara” was the identity of UPN "Veteran" of East Java. The character of State Defense is applied through visual images and then implemented into various souvenir products. Souvenir image implementation process is done by screen printing technique. The process of screen printing is not easy, it requires special skills in the field of graphic design. The stages of the screen printing process will be used as a guide book for the next event. This book is also used as a screen printing practice book for Visual Communication Design students. The method of this research outline through two stages, namely: (1) preparation stage; (2) the stage of creation. The preparation stage includes problem formulation, data collection, analysis, and problem solving. While the stage of creation includes pre-production, production and postproduction.